(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article presents the results of sorting melon seeds using an electrical sorting device, including the voltage values applied to the electrodes and the names of the fractions, the quantity of separation into fractions, as well as the results of studying the mass of 1,000 seeds.